Rules and scope of applying means of witnesses and victims protection and assistance according to the victims and witnesses protection and assistance bill - Żylińska, Justyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
Combating crime using conventional methods is not always sufficient. Witnesses concerned about their life, health, or other goods do not always want to testify. Therefore, it is very important to ensure the sense of safety and mental comfort while they fulfil the role of a witness. Unfortunately, there are still no comprehensive solutions concerning the means and manner of support which would be regulated within the framework of a legal act aimed at protecting the witness and victim in a situation of risk derived from the provision of testimony charging the offender.Under these circumstances, the fact that on 15th July 2014, at its meeting, the Council of Ministers adopted a draft Act on protection and aid to victims and witnesses whose purpose is to establish comprehensive legal regulations concerning the victims and witnesses whose life and health may be at risk, should be regarded as a positive phenomenon.The subject of this paper is an analysis of the regulations contained in the said Act. The paper focuses on the presentation and evaluation of the means ensuring protection and help which may be applied in the situation of risk to life and health of the witness and the victim. It also discusses the premises and manner for granting the aid as envisaged in the newly drafted act.
Keywords: świadek; ochrona świadka; pomoc świadkowi; przestępczość; przestępczość zorganizowana